A Study on The Effect Of Defect Location On Stress In Bending Pipe - KIM, Jin-Bong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, the stress that generated when the first or second root of a corrugated pipe is defective is analyzed. The model is analyzed using F.E.M. code. The boundary conditions of deflection or torsion on the opposite side of the defect in the corrugated pipe are changed. The effect of the defect is evaluated using the change of the stress magnitude and the stress concentration factor(K) according to those conditions. As a result of comparing the stress magnitude, K around the flaw at the secondary root is larger than K around the flaw at the first root. Based on the position of the defect, the stress difference in the 1st root increases depending on the boundary condition of bending deflection. However, when the 2nd root is defective, the stress magnitude is similar in both cases regardless of the bending deflection. The magnitude of the stress generated in the corrugated pipe is the highest when the second root is defective. And the stress magnitude is the lowest when there is no defect. In the absence of defects, the stress gradually increases after the stress reaches the minimum value as the amount of deformation increases. However, if there is a defect, stress continues to increase, and when it passes through the plastic zone, the stress gradually increases.